In her defense : a novel - Malicka, Philippa (Scribner, an imprint of Simon & Schuster, LLC, 2026)
As a sensational celebrity libel trial unfolds, a young woman at the periphery secretly wields the power to make or break the case. But with her own hidden past, will she dare to speak up? Everyone is watching. Only one person knows the truth. The whole country has been riveted by the trial: Beloved TV star and national treasure Anna Finbow, standing in court, accusing her daughter's therapist Jean Guest of brainwashing her daughter Mary for her own financial gain. Jean insists Mary's traumatic memories arise from her upbringing and her time studying at a prestigious art school in Rome; wounds only Jean's therapy can heal. But as the trial unfolds, it's Augusta "Gus" Bird, Anna's former employee--a seemingly insignificant bystander, a nobody--who holds the key to unraveling the tangled web of lies and deceit. What really happened to Mary in Rome? And if her memories can't be trusted, how will they ever uncover the truth behind her estrangement? Twisty and propulsive, In Her Defense is a compulsively readable debut for fans of Lucy Foley and Laura Dave.